CHANGE IN WATER CONTENT OF PATCHOULI LEAVES DURING DRYING PROCESS WITH DIFFERENT AIR STREAM VELOCITIES AND TRAY DRYER ROTATION - Sumarsono Sumarsono (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2005)
Patchouli farmers are often faced with low quantity and quality of the extracted oil produced by the crop. These are primarily due to lack of understanding in the post harvest technology. Purpose of this study was to determine the rate of change in water content of patchouli for the period of drying process at different rate of air stream velocities and to determine the position of drying trays in dryer that provide the shortest period of bringing the plant material into 14% water content for given air stream velocities. Results indicated that the first and second lower trays (tray1 and tray 2) in the dryer provided the shortest period of drying the material at all air stream velocities. At 90 m min-1 velocity, both trays brought the material into 14 % water content at 21th interval of perception (126 h). Similarly, at 110 m min-1 and 125 m min-1 velocities, the same condition was found at 16th interval of perception (96 h) and 18th interval of perception (108 h), respectively.